Kaji Eksperimental Kinerja Turbin Angin Sumbu Vertikal Tipe Darrieus H 4 Blade Profile Naca 2415 Dengan Variasi Sudut Pitch - Kusuma, Muh Wira Tri; Mainil, Rahmat Iman; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Wind energy including renewable energy development. In previous research for the wind turbine of vertical type Darrieus H profile naca 2415 still slightly, thus lifted the title research on the performance of vertical wind turbine type Darrieus H profile naca 2415. The purpose of this research is to find the effect on the performance of the pitch angle for the vertical wind turbine type darrieus H with profile NACA 2415. This research uses experimental method, with varying wind speed and angle of pitch given of the wind speed 3.6 m/s, 4.15 m/s, 5.04 m/s and the variation the angle of pitch 0°, 10°, 20°, with a load of 250 grams. As for capturing data is wind speed and rotation shaft. The results of research on wind speed 3,69 m/s performance turbine are highest in large Angle of pitch 0° , with large value CP = 4,35 %, wind speed 4,15 m/s performance turbine more effective in large angle of pitch 0° , with large value CP = 3,80 % , wind speed 5,04 m/s performance turbine effective in large angle of pitch 0° , with large value CP = 2,42 % .Keyword: Darrieus H, Angle of pitch, Blade, NACA 2415